PERENCANAAN PENGUKURAN KERJA DALAM MENENTUKAN WAKTU STANDAR DENGAN METODE TIME STUDY GUNA MENINGKATKAN PRODUKTIVITAS KERJA PADA DIVISI POMPA MINYAK PT BUKAKA TEKNIK UTAMA TBK. - Rully, Tutus; Rahmawati, Noni Tri (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTThe purpose of this study was to determine the workers planning work measurement, to determine the productivity of the workers, and to determine the measurement of work in improving the productivity of workers. The method used is a case study and one of measurement method used is a work time study. Results and discussion of this research is a discrepancy between theory and phenomena that occur in the company, that there are some workers who use idle time and personal time more than 20% (96 minutes) of total working time. Lack supervision on the discipline of working time and standard time greatly affect the productivity levels of workers. With the use of a good standard time, labor productivity increased as indicated by the number of units produced of two workers from 11 units to 14 units.Â Keyword:Â  Measurement of work, time standards and work productivity standards